Organoantimony (III) Derivative Induces Necroptosis in Human Breast Cancer MDA-MB-231 Cells - Liu, Yong-ping; Lei, Jian; Yin, Ming-Ming; Chen, Yi (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Aim: This study aimed to investigate the anticancer effect and the underlying mechanisms of organoantimony (III) fluoride on MDA-MB-231 human breast cancer cells. Methods: Five cancer and one normal cell line were treated with an organoantimony (III) compound 6-cyclohexyl-12- fluoro-5,6,7,12-tetrahydrodibenzo[c,f][1,5]azastibocine (denoted as C4). The cell viability was detected by MTT assay. Induction of cell death was determined by Hoechst 33342/PI staining and Annexin-V/PI staining. The effect of C4 on the necroptotic relative protein was determined by Western blot analysis. Results: Among the five cancer cell lines, C4 decreased the viability of MDA-MB-231, MCF-7 and A2780/cisR, and showed less toxicity on normal human embryonic kidney cells. In breast cancer cell line MDA-MB-231, the C4 treatment induced necrotic cell death as well as LDH release in a time- and dose-dependent manner. Moreover, C4 could increase the expression of phosphorylated RIPK3 and MLKL proteins. Overall, the C4 treatment resulted in the reduction of mitochondrial transmembrane potential and accumulation of ROS in MDA-MB-231 cells. Conclusion: C4-induced necroptosis could be ascribed to glutathione depletion and ROS elevation in MDA-MB-231 cells. Our findings illustrate C4 to be a potential necroptosis inducer for breast cancer treatment.
Keywords: oxidative stress